Status Hukum Pernikahan Colong Mempelai Wanita di Desa Sraten Kecamatan Cluring Perspektif KHI dan Adat - Fawait Syaiful Rahman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2019)
Abstract: The definition of marriage and its purpose in the Compilation of Islamic Law is stated in article 2 that is, the marriage according to Islamic Law is marriage, that is a very strong contract of duty to obey God's commands and to implement it is worship and Article 3 that is, Marriage aims to realize the life of a household that sakinah, mawaddah, and rahmah. Marriage is an inner born bond between a man and a woman as a husband and wife with the aim of forming a happy and eternal family based on the Supreme Godhead. The above definition is contained in Act No. 1 of 1974 on Marriage. Marriage has a very close relationship with religion, so marriages not only have physical / physical elements, but also have inner / spiritual elements that have an important role in life. Sraten village, Cluring subdistrict, Banyuwangi district is one of the villages in Banyuwangi with different cultures in marriage. In the village of Sraten there is a marriage where a prospective bride is kidnapped by the man. According to information on observation and interim interview information to informal grandchildren such practice has been passed down to generations, so it is not taboo anymore, because not just one or two times, the practice of marriage with a kidnapped female candidate has been done a lot. Therefore, according to researchers it is important to be more in-depth on the basis of appropriate research theory and methodology so as to produce credible and scientifically accountable data. It is concluded based on the distinction between the theoretical and field data analysis that the marriage collateral that occurs in the Sraten Village of his law is legitimate, since the wedding of the colong is not substantive in terms of the terms and the rukun pernikahan, but the wedding of the colong is just an expression or name of a custom in a the area in this case is the Sraten village community with the aim of maintaining the relationship between the two lovers so that the spouses are involved. Furthermore, the views of the Sraten village community towards the colong marriage during the marriage are approved by both families and guardians from the parties who are willing to guard, the legal status of the marriage is valid and there is no problem.